Cursinhos populares e o acesso ao ensino superior: contribuições para além do conteúdo - Ana Thereza Reis Magalhães (2018)
This work aims to understand how college preparatory social courses contribute to students education beyond teaching college application contents. In that way, based on Bourdieu's theory and concepts of cultural capital and social capital, as well as on studies that address the issue of those preparatory courses, this research examined how these contributions are elaborated in the school life of Equalizar preparatory course, located at the Federal University of Minas Gerais (UFMG), Belo Horizonte city. The research process included questionnaires, observations and interviews. The questionnaires were applied to students of the preparatory course in order to discover and outline some of their general characteristics such as family socioeconomic status, school background and awareness of the application processes to higher education. The interviews were conducted with the president of the course, four teachers, two members of the Núcleo Psicopedagógico (Nap) and five students. Moreover, observations were conducted in classes in order to comprehend the everyday reality of the course. The contributions identified can be classified into two aspects, one directly related to the application processes and another related to a broader citizenship education. Concerning college application processes, the course not only helps with learning contents, but also assists on choosing their degree and better strategies to the admission exams. Furthermore, students have the opportunity to get to know UFMG and its various activities before accessing higher education, which will probably help them in university life. Another contribution pointed out in this research concerns the autonomy developed by the students and the friendship between these students and their teachers. Regarding the broader education, a point that stands out is the "solidarity network" establishment, since volunteer work supports the preparatory course, this experience awakens the students desire to contribute to similar activities, including the possibility of volunteering at Equalizar later. Moreover, the preparatory course encourages the students to build selfconfidence, self-esteem and is concerned with anxiety, which helps the students prepare not only for the exams but for life as a whole. Therefore, besides expanding the students cultural and social capital, Equalizar deals with aspects that, even though not the main requirements for college admissions, not only help the application process, but are also a decisive differential for the permanence of students from lower working classes in higher education.